Turning a Targeting β-Catenin/Bcl9 Peptide Inhibitor into a GdOF@Au Core/Shell Nanoflower for Enhancing Immune Response to Cancer Therapy in Combination with Immune Checkpoint Inhibitors - Weiming You; Fang Ma; Zhang Zhang; Jin Yan (MDPI AG, 2022)
Combination administration is becoming a popular strategy in current cancer immunotherapy to enhance tumor response to ICIs. Recently, a peptide drug, a protein-protein interaction inhibitor (PPI), that disrupts the β-catenin/Bcl9 interaction in the tumoral Wnt/β-catenin pathway has become a promising candidate drug for immune enhancement and tumor growth inhibition. However, the peptide usually suffers from poor cell membrane permeability and proteolytic degradation, limiting its adequate accumulation in tumors and ultimately leading to side effects. Herein, a gadolinium-gold-based core/shell nanostructure drug delivery system was established, where Bcl9 was incorporated into a gadolinium-gold core-shell nanostructure and formed GdOFBAu via mercaptogenic self-assembly. After construction, GdOFBAu, when combined with anti-PD1 antibodies, could effectively inhibit tumor growth and enhance the response to immune therapy in MC38 tumor-bearing mice; it not only induced the apoptosis of cancer cells, but also promoted the tumor infiltration of Teff cells (CD8+) and decreased Treg cells (CD25+). More importantly, GdOFBAu maintained good biosafety and biocompatibility during treatment. Taken together, this study may offer a promising opportunity for sensitizing cancer immunotherapy via metal-peptide self-assembling nanostructured material with high effectiveness and safety.